Diagnosis dan Tatalaksana Terkini Penyakit Neurosistiserkosis - Michael Carrey; Endy Suseno; Freggy Spicano Joprang; Octavianus Darmawan; Rr. Josephine Retno Widayanti (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Cysticercosis occurs in porcine naturally. A human can be infected by cysticercosis if they swallow Taenia solium's egg inadvertently. These eggs can be found in vegetables or unboiled water. These eggs hatch and later will become larva that becomes cysts in muscle or brain, known as cysticercus cellulose. Neurocysticercosis is an infection of the central nervous system caused by Taenia solium at its larval stage. Indonesia is a developing country with a high incidence rate of neurocysticercosis, with the highest amount of cases found in Bali and Papua. Neurocysticercosis boasts a broad array of clinical symptoms, from silent disease to a severe, debilitating illness that leads to death. The diagnosis of neurocysticercosis itself presents a great challenge, due to the unspecific clinical symptoms, in-pathognomonic radiographic findings and serologic studies with low specificity and sensitivity. The management of neurocysticercosis consists of a combination of antiparasitic agents and supportive therapies, ranging from steroid to surgeries that can be done under certain circumstances.